Encapsulation of Lemongrass Extract (Cymbopogon citratus) Coated Alginate/Chitosan Using Gelation Method - Aji Prasetyaningrum; Sadam Arrois; Fitri Lafifa; Aat Zaki Mubarok; Fadlillah Fani; Noer Abyor Handayani; Ratnawati Ratnawati; Bakti Jos (Reaktor, 2021)
Lemongrass (Cymbopogon citratus) is a medicinal plant with various biological activities such as antibacterial, antifungal, antiprotozoal, anti-inflammatory, and antioxidant. This study aimed to encapsulate lemongrass bioactive in alginate/chitosan complex by enhancing the properties of CaCl2 crosslinked incorporated with tween 80 by ionic gelation method. The hydrogel was prepared by mixing alginate solution (2% w/v) and chitosan solution (1% w/v) with a ratio (1:1 v/v). Tween 80 (2% v/v) was added as a dissolution enhancer and CaCl2 as a crosslinker agent. The formulation varying by concentration of CaCl2 (0.1M to 0.3M) and lemongrass extract (2% to 12%). Encapsulation lemongrass with alginate-chitosan beads is characterized to determine encapsulation efficiency, swelling study, morphology, functional groups, and release study. The results showed that encapsulation efficiency ranged from 74.81% to 83.07%. Encapsulation efficiency increased with the addition of CaCl2 and lemongrass extract concentration. The swelling ratio ranged from 27.29 to 37.81, it will decrease with the addition of CaCl2 and lemongrass extract concentration. The Scanning Electron Microscopy (SEM) analysis of hydrogel beads shows a polyhedral shape, porous, and rough surface which indicates bioactive of lemongrass trapped on the beads. The Fourier Transform Infrared Spectroscopy (FTIR) results show new peaks at 1734 cm-1 as carbonyl stretch vibrations in ketones, aldehydes, and carboxylic acids, indicating the addition of lemongrass extract. Bioactive of lemongrass extract loaded alginate-chitosan beads was successfully released as much as 87.12% at pH 6.8. This study suggested the strong potential alginate-chitosan beads as an encapsulating agent for lemongrass extract using the ionic gelation method, and it has potential as a drug delivery system.Keywords: encapsulation; lemongrass; alginate; chitosan; CaCl2